GAMBARAN SELF-COMPASSION PERAWAT INSTALASI GAWAT DARURAT DI JAKARTA - Adinda, Puspa Triani; Aryanto, Christ Billy; Tunjungsari, Laurensia Harini (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2020)
Abstract ?  This study aims to explore how self-compassion shapes the experience of hospital nurses in Emergency Department (ED) in Jakarta. Previous studies demonstrated that the lack of self-compassion can increase compassion fatigue, thereby reducing the quality of services and eventually affect patients? well-being. Mixed-methods design was employed by collecting data from 77 nurses through convenient sampling. Two nurses with highest self-compassion scores and a nurse with lowest self-compassion score were interviewed for further analysis. The descriptive result indicated that self-compassion of ED nurses in Jakarta was considerably high and only one nurse had relatively low self-compassion. There was a significant difference in self-compassion based on working time and hospital types. Qualitative analysis indicated that under stressful circumstances, nurses with high self-compassion tended to engage with various religious activities, while the one with low self-compassion tended to be self-indulging.Abstrak ? Penelitian ini bertujuan untuk mengeksplorasi self-compassion perawat rumah sakit bagian Instalasi Gawat Darurat (IGD) di Jakarta. Studi sebelumnya menunjukkan bahwa kurangnya self-compassion dapat meningkatkan rasa lelah secara mental, sehingga menurunkan kualitas pelayanan rumah sakit dan dapat berdampak pada kesejahteraan pasien. Desain mixed-methods digunakan dengan mengambil 77 sampel perawat dari berbagai tipe rumah sakit melalui teknik sampel convenient. Dua perawat dengan self-compassion tertinggi dan satu perawat dengan self-compassion terendah diwawancarai untuk analisa data kualitatif. Hasil deskriptif mengindikasikan bahwa self-compassion perawat IGD di Jakarta tergolong tinggi dan hanya satu perawat yang ditemukan memiliki self-compassion rendah. Terdapat perbedaan signifikan mengenai self-compassion perawat berdasarkan lama bekerja dan tipe rumah sakit. Hasil kualitatif mengindikasikan bahwa ketika stres, perawat dengan self-compassion tinggi cenderung melakukan aktivitas religius, sementara perawat dengan self-compassion rendah cenderung melakukan self-indulgence.